DIGITAL TRANSFORMATION TO SPUR WOMEN EMPOWERMENT IN MSMES: A CASE STUDY APPROACH - Khandelwal, Rakhi; Ashutosh Priya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Empowered women are important to uplifts their economic, social, and political status. Women entrepreneurship refers to women who initiate, organize, manage, and operate business enterprises. As Jawaharlal Nehru aptly put it, “To awaken the people, it is the women who must be awakened. Once she is on the move, the family moves, the village moves, the nation moves”. Despite women constituting nearly 50% of the world’s population, India looks a comparatively lower female population than males. Socially, women are often not treated as equals to men. However, in modern society, they are breaking barriers and engaging in miscellaneous activities, including business ventures. Micro, Small, and Medium Enterprises (MSMEs) play a vital role in industrial development. According to the Ministry of MSME, this sector employs over 110 million people through more than 63 million enterprises, significantly contributing to India’s Gross Domestic Product (GDP). MSMEs account for approximately 30% of the GDP and are crucial drivers of economic growth. This paper would explore how digital transformation in MSMEs has empowered women entrepreneurs by providing them with new opportunities for growth, market access, and financial independence. The study could include case studies of successful women-led MSMEs that have embraced digitalization.